Biology and Interaction of the Natural Occurrence of Distinct Monopartite Begomoviruses Associated With Satellites in Capsicum annum From India - Mishra, Megha; Verma, Rakesh Kumar; Marwal, Avinash; Sharma, Pradeep; Gaur, R. K. (Frontiers in Microbiology, 2020)
Chilli (Capsicum annuum L.) is an important vegetable and spice crop of tropical and sub-tropical regions. Chilli plants showing upward leaf curling, leaf crinkling, and leaf yellowing symptoms, collected from Sikar district of Rajasthan, India, were found to be associated with begomovirus and satellite molecules. The presence of virus was confirmed by PCR using virus-specific primer. The full-length genomic DNA-A of three begomovirus (MM-1, CS-1 and RV-1) and two satellites (MM-2 and MM-3) were cloned which was identified from single symptomatic chilli plant. The genome organization of isolated three viruses is similar to those of other Old World monopartite begomoviruses. The comparison of the sequences and closest phylogenetic relationships for the begomoviruses, betasatellite and alphasatellite DNAs revealed that MM-1 was designated as DNA-A of Chilli leaf curl virus (ChiLCV), CS-1 is considered to be a new distinct species of Tomato leaf curl Gujrat virus (ToLCGV) whereas RV-1 as a new strain of Cotton leaf curl Multan virus (CLCuMuV). The DNA-A component of ChiLCV showed 8.6%, ToLCGV of 16.6% and CLCuMuV of 7.7% average evolutionary divergence, concomitantly, the betasatellite and alphasatellite molecule had 9.9% and 5.9% overall sequence divergence, respectively. Interestingly, most of the begomoviruses were found to be intra-species recombinants. The dN/dS ratio and Tajima D value of all viral DNA-A component and their associated betasatellite showed their selective control on evolutionary relationships. The nucleotide substitution rates were determined for the DNA-A genomes of ChiLCV (7.22x10-4 substitutions site-1 year-1), CLCuMuV (1.49x10-4 substitutions site-1 year-1), ToLCGV (7.47x10-4 substitutions site-1 year-1), the genome of associated ChiLCB (4.20x10-4 substitutions site-1 year-1) and CLCuMuA (1.49x10-4 substitutions site-1 year-1). Agro-inoculation studies indicate that the presence of DNA betasatellite induce severe symptoms in N. benthamiana and chilli, suggesting prerequisite association for typical disease development.